Elevated Glucose-Potassium Ratio Predicts Preoperative Rebleeding in Patients With Aneurysmal Subarachnoid Hemorrhage - Wang, Jiayin; Feng, Qiangqiang; Zhang, Yinbin; Qiu, Weizhi; Gao, Hongzhi (Frontiers in Neurology, 2022)
Introduction: Recent reports revealed that higher serum glucose-potassium ratio (GPR) levels at admission were significantly associated with poor outcomes at 3-months following aneurysmal subarachnoid hemorrhage (aSAH). This study aimed to investigate the association between GPR and the risk of rebleeding following aSAH. Methods: This single-center retrospective study of patients with aSAH was conducted in our hospital between January 2008 and December 2020. Patients meeting the inclusion criteria were divided into the rebleed group and the non-rebleed group. Univariate and multivariate analyses were implemented to assess the association between risk factors of rebleeding and outcomes. Results: A total of 1367 patients experiencing aSAH, 744 patients who met the entry criteria in the study (mean age, (54.89±11.30) years; 60.50% female patients), of whom 45 (6.05%) developed rebleeding. The patients in the rebleed group had significantly higher GRP levels than those of patients without rebleeding (2.13(1.56-3.20) vs. 1.49(1.23-1.87); p＜0.001). Multivariable analysis revealed that higher mFisher score and GRP were associated with rebleeding (mFisher grade, Odds ratios (OR) 0.361, 95% confidence interval (CI) 0.166-0.783, p=0.01; GPR, OR 0.254, 95% CI 0.13–0.495, p<0.001). The Receiver-operating characteristics (ROC) analysis described that the suitable cut-off value for GPR as a predictor for rebleeding in aSAH patients was determined as 2.09(the area under the curve (AUC) was 0.729, 95% CI 0.696–0.761, p<0.0001; the sensitivity was 53.33%, and the specificity was 83.98%). Pearson correlation analysis showed a significant positive correlation between GPR and mFisher grade, between GPR and Hunt-Hess grade (mFisher grade r=0.4271, OR 0.1824, 95%CI 0.3665-0.4842, p＜0.001; Hunt-Hess grade r=0.4248, OR 0.1836, 95%CI 0.3697-0.4854, p＜0.001). The patients in the poor outcome had significantly higher GRP levels than those of patients in the good outcome (1.87(1.53-2.42) vs. 1.45(1.20-1.80); p＜0.001). Multivariable analysis demonstrated that GRP was an independent predictor for poor prognosis. The AUC of GPR was 0.709 (95% CI 0.675–0.741; p＜0.0001) (Sensitivity=77.70%; Specificity=55.54%) for poor prognosis. Conclusions: Higher preoperative serum GPR level was associated with Hunt–Hess grade, mFisher grade, rebleeding, and unfunctional outcome, and that they predicted preoperative rebleeding and the 90-days outcome of non-diabetic aSAH patients, which had potentially relevant clinical implications in patients with aSAH.